Production and characterization of synbiotic Doogh by gum tragacanth, date seed powder, and L. casei. Issue 11 (1st August 2022) - Farahani, Minoo Vasheghani; Sedaghati, Marjaneh; Mooraki, Nargess
Abstract: Doogh is a traditional fermented Iranian drink. In this study, the effect of gum tragacanth dispersion (GTD) (0, 0.25%) and palm kernel powder (PKP) (0, 0.5%, and 1.5%) on the physicochemical, microbial, and sensory properties of Doogh during 22 days of storage was evaluated. The results revealed that the stability against phase separation and viscosity of Doogh samples containing GTD alone and combinations of GTD and PKP were higher than control samples. Herschel‐Bulkley model was an appropriate model for describing the flow behavior of Doogh formulated with GTD and PKP, while power‐law model was suitable model for control sample. Although GTD had insignificant effect on Lactobacillus casei (L. casei) viability, PKP improved its viability. Also, the samples treated with 0.25% GTD and 0.5% PKP ( T 4 ) had proper general acceptability score on the 22nd day. Finally, the T 4 treated sample was chosen as the best formulation for synbiotic Doogh production. Novelty impact statement: Physical instability and loss survival of probiotic bacteria are the most important problems in the production of synbiotic Doogh . Gum tragacanth dispersion and date seed powder were used as effective components to overcome these problems. The Doogh samples containing the gum alone and the mixture of gum and date seed powder showed a higher stability compared with the control sample. Doogh sample containing 0.5% gum and 0.5% date seed powder had proper number of probiotic and overall acceptability score; therefore, this sample can be considered as the best formulation for the production of a synbiotic Doogh .